Beliefs and myths about women who suffer gender-based violence: Interpretations of a group of young adults based on an awareness-raising campaign - San Martín Martínez, Conchi (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study analyzes the beliefs and myths of 30 young people about the feelings of a woman victim of gender violence. Materials used were governmental awareness-raising campaign. Findings show a victim mainly ashamed or guilty; secondly sad and helpless, and thirdly brave and motivated. Furthermore, only 40% consider that the advertisements helps the woman. We detect an important persistence of the myth that holds the victim responsible for being unable to change her situation. Nevertheless, there is also a questioning of this myth and an evolution towards less distorted beliefs.